Innovation levels in the economies of Central and Eastern Europe - Stefan Krajewski (Comparative Economic Research. Central and Eastern Europe, 2014)
When the countries of Central and Eastern Europe entered the European Union, they were given the opportunity to become transformed into knowledgebased societies, with modern, innovation-oriented economies which build their strength and competitiveness on the development of native technical solutions and concepts. To achieve this, however, requires a lot of effort and radical and profound changes in comparison with the previous situation. New priorities and strategic objectives and methods of their implementation (including innovation strategies) must be developed, financial and in-kind resources reallocated, and social and technical infrastructure must be expanded and modernized. These are difficult challenges, but their effective implementation is essential so that the CEECs can avoid marginalization and become equal partners within the EU. The statistical data presented in this paper indicates that the innovative position of the CEECs is still unfavourable and relatively weak, with the exception of Slovenia and Estonia. Poland is in a particularly difficult situation, with many signs of stagnation with respect to innovation, keeping it at a low level (next to Bulgaria and Romania).
Keywords: 330; innovation; competitiveness; Central and Eastern Europe; European Union